Competências operacionais em redes de manufatura: uma análise sob a perspectiva coevolucionária - Biazzin, Cristiane (2015)
This dissertation aims to evaluate how operational competences dissemination between headquarters and manufacturing network evolve. The main objective can be split into five secondary objectives: (i) Define the concept of operational competences (ii) Identify the possible factors that impact operational competences dissemination within manufacturing networks through its actors perception; (iii) Identify the relationship between those factors; (iv) Investigate and analyze how organizations are structured in order to promote operational competences sharing process, observing its dynamics and the interaction between actors; (v) Evaluate how the combination of internal factors (micro level) and externalities (from competitive environment) impact and are impacted by this dynamics. For doing so, two qualitative researches on Operations Management field were developed by using Coevolutionary Theory. The very first study, an exploratory research, aims to identify the antecedents of operational competences dissemination. It was developed initially a focus group research, followed by semi-structured interviews with Operations Executives. It was possible to identify and rank the main factors that impacts the dissemination process. The second one, is a multiple case study. Four manufacturing networks were investigated in order to draw the coevolutionary process. The results show that coevolution within manufacturing networks and operational competences dissemination is a gradual process, it contains cumulative motivational factors, involves actors from different dimensions and with absorptive capacity. The findings show that it is possible to identifiy that operational competences building maturity evolves with manufacturing maturity process.